Proceedings of the Thirtieth Annual ACM-SIAM Symposium on Discrete Algorithms 2019
DOI: 10.1137/1.9781611975482.28
|View full text |Cite
|
Sign up to set email alerts
|

An Algorithmic Blend of LPs and Ring Equations for Promise CSPs

Abstract: Promise CSPs are a relaxation of constraint satisfaction problems where the goal is to find an assignment satisfying a relaxed version of the constraints. Several well known problems can be cast as promise CSPs including approximate graph and hypergraph coloring, discrepancy minimization, and interesting variants of satisfiability. Similar to CSPs, the tractability of promise CSPs can be tied to the structure of associated operations on the solution space called (weak) polymorphisms. However, compared to CSPs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
116
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(116 citation statements)
references
References 33 publications
0
116
0
Order By: Relevance
“…Fortunately, building on the initial insights and results in [1,9,11,10], it was observed in [14] (among many other important results such as the NPhardness of 5-coloring a 3-colorable graph) that the basics of the CSP theory from [4] generalize to PCSPs. In particular, the notions of pp-constructions and polymorphisms have their PCSP counterparts and the connection between relational and algebraic structures works just as well as in the CSP.…”
Section: Promise Cspsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fortunately, building on the initial insights and results in [1,9,11,10], it was observed in [14] (among many other important results such as the NPhardness of 5-coloring a 3-colorable graph) that the basics of the CSP theory from [4] generalize to PCSPs. In particular, the notions of pp-constructions and polymorphisms have their PCSP counterparts and the connection between relational and algebraic structures works just as well as in the CSP.…”
Section: Promise Cspsmentioning
confidence: 99%
“…A fundamental question is whether each finite tractable PCSP template can be pp-constructed from an infinite tractable CSP template. In [10], the authors conjectured that the answer is positive and even suggested a family of tractable CSPs that might solve all Boolean PCSPs.…”
Section: Finite Pcsps Are Infinitarymentioning
confidence: 99%
See 1 more Smart Citation
“…This problem, even its search version, admits elegant polynomial time algorithms [14,15] -one is based on solving linear equations over the integers, another one on linear programming. For this specific template, the algorithm can be further simplified as follows.…”
Section: Examplesmentioning
confidence: 99%
“…After the introduction of the PCSP framework, it has quickly turned out that both the notion of a polymorphism and Theorem 2.10 have straightforward generalizations. Any PCSP whose template (over the domains E 2 and E 2 ) admits all these polymorphisms is in P [14,15]. sketch.…”
Section: Th Step: Minor Conditions!mentioning
confidence: 99%